Use of plant oils from the southwestern Amazon for the control of maize weevil. (July 2015) - Santos, A.C.V.; Fernandes, C.C.; Lopes, L.M.; Sousa, A.H.
Abstract: The purpose of this study was to evaluate the insecticidal potential of oils obtained from plant species endemic to the southwestern Amazon region against the maize weevil ( Sitophilus zeamais Motschulsky). We evaluated the mortality of insects treated with 11 plant oils. After the discriminant assays, concentration–mortality bioassays were conducted to evaluate the toxicity of each oil. The insects were treated with the oils, and mortality was assessed after 24 h. Each assay was performed in four replicates. The LC50 of the oils against S. zeamais ranged between 53.35% and 65.22% for the oils obtained from Astrocaryum aculeatum Meyer, Copaifera spp., Carapa guianensis Aublet, Oenocarpus bataua Mart., Mauritia flexuosa L, . and Orbignya phalerata Mart. These oils exhibited consistency in their toxic activity and emerged as potential alternatives to be implemented in integrated pest management programs for stored product pests. The results of this investigation identified several plant species in the Amazonian flora with potential insecticidal properties. Highlights: The Amazonian flora features a variety of plants with insecticidal properties. Eleven oils obtained from plants endemic to the Amazon region have toxic effects on Sitophilus zeamais Motschulsky. Oils obtained from six plant species exhibited consistent toxic activity.